A New Method for Two-Dimensional Analysis of Jaw Movements in Bruxism during Sleep - NAKAGAWA, Hirochika; SHIMIZU, Manabu; KATO, Hiroshi; KATO, Yoshihiro; INABA, Akito; KOWASHI, Yusuke; TAKAMATSU, Takatsune; SAWADA, Ayako (Nihon Shishubyo Gakkai Kaishi (Journal of the Japanese Society of Periodontology), 1994)
The purpose of this study was to develop a new method for analying jaw movements during sleep and to observe the jaw movements by using this apparatus. A two-dimensional (antero-posterior and lateral) jaw movement recording system was developed to assess bruxism during sleep. The accuracy of this system was checked. The jaw movement data of 6 male and 1 female adult volunteers, 25 to 35 years of age (mean: 29.3 years) were examined for one night. In addition, data for masseter muscle activity were obtained by EMG. The results obtained were as follows; 1) The accuracy of this system was equal to MKG in its ability to describe jaw movements in the horizontal plane. 2) This system was able to record jaw movements during grinding and clenching. In each subjects, grinding was divided into as many as three types according to the jaw movement pattern, but the patterns of jaw movements were similar in some types of grinding. 3) The clenching positions during sleep were centric occlusion and other lateral positions. Many clenching positions were observed on the locus of jaw movements of grinding patterns. These findings suggest that our jaw movement recording system is able to record a jaw movements during sleep, and may be useful in assessing the mechanisms of acceleration of the progression of periodontal lesions by bruxism.